Equilibrium Real Exchange Rate, Misalignment, and Export Performance in Developing Asia - Juthathip Jongwanich (Asian Development Bank (ADB), 2009)
This paper examines the equilibrium real exchange rate and real exchange rate misalignments in developing Asian countries during the period 1995–2008. In addition, the relationship between real exchange rate misalignment and export performance is investigated. In the lead-up to the 1997–1998 financial crisis, real exchange rate exhibited persistent overvaluation in the crisis-affected countries. After the crisis, real exchange rate undervaluation was evident in many Asian countries such as People's Republic of China (PRC), Malaysia, and Thailand. This study also shows that real exchange rate misalignment could have a negative impact on export performance in developing Asia. With its implications on economic activity, monitoring real exchange rate equilibrium and misalignment is a useful tool for governments/central banks to ensure balance in the economy.
hdl:11540/1798
Keywords: F12; F41; O11; O53; 330; Open Macroeconomics; Real Exchange Rate; Exports; East and Southeast Asia; Kaufkraftparität; Handelseffekt; Schätzung; Asien